Which shows 602 − 402 being evaluated using the difference of squares method?

602 − 402 = (3600 + 1600)(3600 − 1600) = 10,400,000
602 − 402 = 3600 − 1600 = 2,000
602 − 402 = (60 − 40)2 = 202 = 400
602 − 402 = (60 + 40)(60 − 40) = (100)(20) = 2,000

Respuesta :

Hagrid
The right answer for the question that is being asked and shown above is that: "602 − 402 = (3600 + 1600)(3600 − 1600) = 10,400,000" The equation that shows 602 − 402 being evaluated using the difference of squares method is that 602 − 402 = (3600 + 1600)(3600 − 1600) = 10,400,000

Answer:

A

Step-by-step explanation: